UKURAN ANTHROPOMETRI ANAK SD PENDERITA GONDOK DI KABUPATEN JEMBER - Ari Tri Wanodyo Handayani (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2011)
Iodine is an essential element for humans. It is concentrated in the thyroid gland and become a vital component of thyroid hormones. Reduced concentration of iodine causes iodine deficiency disorders (IDD) are often called goiter. Thyroid hormone produced by the thyroid gland directly affect bone growth, bone maturation and physical height. Anthropometry is often used to measure the nutritional status of community. This study aims to determine the differences in anthropometry of goitrous and normal children.This study was an observational-analytic study with cross-sectional data. The sample was children of primary school, aged 72-90 months in the Sumbersari and Mayang subdistrict, Jember. Sample size was 100 people each group. The data collected was the degree of goiter (palpation method), physical height (using microtoise) and body weight (using a digital scale). The measurement results are also calculated based on the Z-score.Analysis of data using t-test.The results showed that average physical height of goitrous children was 113.53 ± 5.20 cm and the value of Zscore was -1.28 ± 0.98 SD. In non goitrous children average physical height was 117.59 ± 8.40 cm and -0.94 ± 1.41 SD (Zscore values). The average body weight of goitrous children was 18.5 ± 3.40 kg and -0.97 ± 1.13 SD (Z-score values). The average body weight of non goitrous children was 20.68 ± 10.82 kg and -0.18 ± 1.46 SD (Z-score values). T-test analysis results indicate the existence of differences in physical height and body weight in goitrous children and non goitrous children were significant. Physical height is associated with chronic malnutrition. Hypothyroidism in goitrous patients may reduce the secretion of T3 and T4 hormones, which are growth hormone. Decreasing it can inhibit accretion of linear growth (height) and becomes stunted. Chronic malnutrition that occurs in goitrous children may also predispose to nutritional balance disturbances occurred that resulted in acute malnutrition so the weight is low, as a result of decreased appetite, illness (eg diarrhea, respiratory infections), or due to lack of sufficient food is consumed